2020
DOI: 10.1088/1742-6596/1529/4/042064
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mobile Application in Learning Malay Foreign Language

Abstract: The use of new technologies has impacted effectiveness in learning which contributes to the smoothness of language performance. The language implication involves all subjects, including Malay foreign language. For instance, the use of mobile learning has been shown a considerable and dynamic potential in learning Malay foreign language. Mobile application usage enables a variety of teaching innovations that assist educators and students in pursuing knowledge and language skills. Thus, this concept paper aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The prevalence of mobile phones among Arabs and the availability of good mobile infrastructure are essential factors that can facilitate the transition to m-learning. In addition, many studies [23][24][25][26][27][28][29][30][31] indicate a positive attitude to and perception of m-learning in various Arab educational institutions.…”
Section: Features Of Using Mobile Applications In Different Countriesmentioning
confidence: 99%
“…The prevalence of mobile phones among Arabs and the availability of good mobile infrastructure are essential factors that can facilitate the transition to m-learning. In addition, many studies [23][24][25][26][27][28][29][30][31] indicate a positive attitude to and perception of m-learning in various Arab educational institutions.…”
Section: Features Of Using Mobile Applications In Different Countriesmentioning
confidence: 99%
“…There are numerous advantages to using a mobile application in the foreign language classroom. Sung et al (2020) investigated the use of mobile applications in learning the Malay language. According to their findings, in order to assist learners in creating their information and ideas, they can communicate and exchange them more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that mobile devices as learning tools promote motivation, learner autonomy and creativity and they help students to develop IT skills (Arvanitis, Krystalli & Panagiotidis, 2016). It is very important that an application for foreign language learning can encourage students to identify the phonetic aspects of a foreign (Sung & al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates also that "mobile-assisted language learning helps to create language immersion, which effectively motivates the learners further" (Shi, Luo, & He 2017, p. 1) and that "mobile devices such as laptops, personal digital assistants, and mobile phones have become a learning tool with great potential in both classrooms and outdoor learning" (Sung, Chang & Liu, 2016, p. 252). It is obvious fact that mobile application usage can enable a variety of teaching innovations that assist students in pursuing knowledge and language skills (Sung & al., 2020). Furthermore, using new technologies in the classroom is now a justified practice as digital technology is part of the everyday life for this decade's learners.…”
Section: Literature Reviewmentioning
confidence: 99%